Gestational diabetes mellitus, Vitamin D status and fetomaternal outcome - T., Rekha; Parveen, Shazia; Noor, Nasreen; Hakim, Seema; Moin, Shagufta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Diabetes is the most common medical complication of pregnancy. Vitamin D deficiency which was initially considered only to influence bone metabolism, is now known to exert a wide spectrum of extra-skeletal effects. Vitamin D deficiency is closely associated with gestational diabetes mellitus, it also leads to adverse maternal and child outcome. Objective of this study was to compare the vitamin D levels in healthy pregnant women and women with gestational diabetes mellitus and to observe the feto-maternal outcome. Methods: This prospective study was carried out on 160 pregnant women between the age group 20-40 years attending the Obstetrics and Gynaecology department of JNMC, AMU, Aligarh from October 2016 to October 2018. Women were divided into group A- normal pregnant women and group B- women with GDM. Estimation of vitamin D was done in both the groups. Results: Mean vitamin D levels were lower in women with GDM as compared to normal pregnant women. Conclusions: Women with vitamin D deficiency have an increased risk of developing GDM and adverse feto maternal outcome as compared to those who had normal level of vitamin.